1971
DOI: 10.4141/cjas71-092
|View full text |Cite
|
Sign up to set email alerts
|

Loss in Digestible Nutrients When Ensiled Barley Is Fed Whole

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
1

Year Published

1976
1976
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 3 publications
1
6
1
Order By: Relevance
“…Assuming that grains were broken only during eating and rumination, then chewing was responsible, on average, for breaking 59, 46 44 and 38% of the intake of oats, wheat, barley and sorghum respectively. The value for oats is appreciably lower than the 88% reported by Shaw and Norton (1906) for cows, and for barley it was lower than Nicholson, Gorrill and Burgess (1971) found with 3-yr-old steers given high moisture grain and hay. Fitch and Wolberg (1934) observed approximately 43% sorghum excreted whole by cows; no values have been found for wheat.…”
Section: Discussioncontrasting
confidence: 72%
“…Assuming that grains were broken only during eating and rumination, then chewing was responsible, on average, for breaking 59, 46 44 and 38% of the intake of oats, wheat, barley and sorghum respectively. The value for oats is appreciably lower than the 88% reported by Shaw and Norton (1906) for cows, and for barley it was lower than Nicholson, Gorrill and Burgess (1971) found with 3-yr-old steers given high moisture grain and hay. Fitch and Wolberg (1934) observed approximately 43% sorghum excreted whole by cows; no values have been found for wheat.…”
Section: Discussioncontrasting
confidence: 72%
“…The decrease in OM digestibility of 014 when whole rather than rolled grain was included in the 0-90 concentrate diet is similar to that reported by Nicholson et al (1971) where rolling proportionately increased the digestibilities of DM, OM and energy of whole ensiled barley by 01 and 0-25 to 0-30 when yearling or 3-year-old steers, respectively, were given diets containing the barley. Morgan and Campling (1978) offered a diet containing 040 whole or rolled barley to 17-monthold steers.…”
Section: Utilization Of Whole Grain By Cattlesupporting
confidence: 78%
“…It is well known that the digestibility of barley is improved by processing (Nicholson, Gorrill and Burgess, 1971; Morgan and Campling, 1978;0rskov, 1979) and limited data suggest that substantial improvement in animal performance in slowly growing cattle will result when barley is rolled (Morgan, Males and Nelson, 1987). There is, however, a need for more data concerning the response to processing of barley when it is included in low proportions in the diet even though McDonald and Hamilton (1980) found that the relative digestibility of whole and rolled oats was not markedly influenced by their proportions in the diet.…”
Section: Introductionmentioning
confidence: 98%
“…Feedlot performance trials with weanling steers have failed to prove advantages for rolled vs. whole high-moisture corn (Loerch and Fluharty, 1998), perhaps because chewing capacity is greater in younger cattle (Nicholson et al, 1971). To our knowledge, there is no information available about the possible interaction between cattle age and the digestibility of whole corn.…”
Section: Introductionmentioning
confidence: 99%